Consulting Activities of Agricultural Economists and Response to University Policies. (9th October 2018) - Conley, Kelsey L.; Lusk, Jayson L.; Parcell, Joe L.; Tonsor, Glynn T.; Gundersen, Craig
Abstract: A perk of academic employment is the ability to earn additional income from non‐university entities by consulting. Despite the availability of such work, the potential synergies with research, teaching, and extension, and the controversy sometimes surrounding it, there is surprisingly little research on the prevalence of outside consulting, the determinants of consulting, or the response of faculty to specific university consulting policies. To address these issues, this paper utilizes data from a nationwide survey of academic agricultural economists. We find that about 43% of the sample reported consulting activities in the year prior to the survey. Of those who consulted, 12% (or about $34, 000) of their total household income on average comes from outside consulting activities. Income from consulting is positively correlated with having a research appointment, income earned from the university, and number of career published papers. We also document extensive heterogeneity across university consulting policies and perceptions of these policies.